ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN KONSUMSI OBAT PADA PASIEN HIPERTENSI DI PUSKESMAS SUNGGAL MEDAN TAHUN 2018 - Parapat, Winny G I; Girsang, Ermi; Nasution, Sri Lestari Ramadhani; Suyono, Tan (Universitasdiwangsa Jambi, 2019)
WHO data (World Health Organization) shows that hypertension sufferers around the world number around 1 billion. The prevalence of hypertension is predicted to continue to increase, in 2025 it is predicted that as many as 29% of adults with hypertension in the world. Based on the results of the Basic Health Research (Riskesdas) the prevalence of hypertension in Indonesia in 2013 was 28,5%, while the prevalence of hypertension in Indonesia in 2017 increased to 30,9%. This study aims to determine the analysis of factors that affect consumption compliance medication in hypertensive patients at the Puskesmas Sunggal Medan. This research is a non-experimental research, namely quantitative research, with a cross sectional research design. The population in this study were all patients suffering from hypertension at the Sunggal Medan Health Center. The population in this study were patients who came to the Sunggal Health Center Medan in August - October 2018, totaling 248 people. The sample used in this study were 45 hypertensive patients who came for treatment at the Sunggal Medan Health Center. The sampling technique uses accidental sampling. The results of this study indicate that there is a significant influence between knowledge with a p-value of 0,002, motivation with a p-value of 0,033, the role of health workers with a p-value of 0,015, and family support with a p-value of 0,000. So the researchers suggested that respondents routinely re-check the Puskesmas to be able to control blood pressure and adhere to taking drugs in the prevention of hypertension and risk factors.